2019
DOI: 10.1002/mop.32061
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative determination of potassium aluminum sulfate dodecahydrate in potato starch based on terahertz spectroscopy

Abstract: Terahertz time‐domain spectroscopy (THz‐TDS) was used to study the additive potassium aluminum sulfate dodecahydrate (PASD) in potato starch. The terahertz time‐domain and frequency domain spectra of potato starch potato starch and PASD were obtained. The absorption coefficient spectrum and refractive index spectrum of the above two substances is calculated. The absorption coefficient spectrum shows that potassium aluminum sulfate dodecahydrate has obvious characteristic absorption peak in terahertz band. THz‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The refractive index n(ω) and absorption coefficient α(ω) can be calculated from Equations ( 2) and ( 3), where φ(ω) is the phase difference between the sample and the reference signal, ρ(ω) is the amplitude ratio of the sample to the reference signal, dis the thickness of sample is, c is the speed of light, and ω is the angular frequency [4].…”
Section: Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The refractive index n(ω) and absorption coefficient α(ω) can be calculated from Equations ( 2) and ( 3), where φ(ω) is the phase difference between the sample and the reference signal, ρ(ω) is the amplitude ratio of the sample to the reference signal, dis the thickness of sample is, c is the speed of light, and ω is the angular frequency [4].…”
Section: Calculation Methodsmentioning
confidence: 99%
“…In order to reduce the error and improve the measurement accuracy, the time-domain signals of the reference signals and the sample signals are measured ten times as shown in Figure 2 [4]. And we take the average of the time delays in Table 1.…”
Section: Time-domain Signal Processingmentioning
confidence: 99%
“…For example, Liu Wen et al [20] used THz spectroscopy to determine the adulterated acacia honey and the final correlation coefficient was 0.985. For example, Liu Jianjun et al [21] used THz spectroscopy to quantify potassium aluminum sulfate dodecahydrate in potato starch and found that potassium aluminum sulfate dodecahydrate had a distinct characteristic absorption peak in the THz band. For example, Zhang Xin et al [22] used THz time-domain spectroscopy and chemometrics to determine amino acid mixtures in cereals and finally proved that THz time-domain spectroscopy could be used for the qualitative and quantitative analysis of amino acids.…”
Section: Carolinementioning
confidence: 99%
“…Terao et al (2018) have studied the boson peak dynamics of natural polymer starch using terahertz time-domain spectroscopy and low-frequency Raman scattering. Liu et al have studied the potassium aluminum sulfate dodecahydrate in potato starch by terahertz spectroscopy qualitatively and quantitatively (Chen, 2013;Liu et al, 2020). Chen, Singh, et al (2018)) used terahertz time-domain spectroscopy to measure glucose levels in the blood of diabetic patients quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…Terahertz spectrum generates terahertz electric field through the interaction between the terahertz pulse and the sample. The waveforms in the time domain and the reference frequency domain are obtained through the fast Fourier transform, and then the waveforms in the frequency domain are processed (Hou et al., 2021 ; Liu & Fan, 2020 ). The absorption coefficient, refractive index, and dielectric constant of the sample can be extracted.…”
Section: Introductionmentioning
confidence: 99%